Analysis of frontier hot spots in teaching and research of internal medicine of traditional Chinese medicine in recent 20 years based on CNKI - Zhen Gao; Maimaititusun Yalikun; Hongying Zhang; Jingcheng Dong (Traditional Medicine and Modern Medicine)
Objective: To understand the research status and hot topics of internal medicine teaching in traditional Chinese medicine (TCM) in recent 20 years. Methods: The relevant literature on the teaching of Chinese Internal Medicine in the past 20 years (2004–2023) was searched in China National Knowledge Infrastructure (CNKI), and the authors, institutions, and keywords were co-occurred and/or cluster analysis by using CiteSpace6.2.R7 and VOSviewer1.6.20 software. Results: A total of 1117 journal articles were included, showing an overall upward trend. The journal with the most published articles is “Chinese Medicine Modern Distance Education of China”, the author is Xiao Yonghua of Dongzhimen Hospital of Beijing University of Chinese Medicine, and the research institution is Henan University of Chinese Medicine, with few cross-team and cross-institutional studies. Keywords “teaching method”, “teaching reform”, “problem-based learning”, “case teaching”, and “clinical teaching” are the research hotspots. “Flipped classroom” and “presentation assimilation discussion” in teaching methods, as well as “curriculum ideology and politics” and “talent cultivation” are possible research directions. Conclusion: Teaching method and teaching reform are the research hotspots of internal medicine teaching in TCM, and the research frontier is the refinement of teaching method, that is, flipped classroom and presentation assimilation discussion, as well as curriculum ideology and politics. However, there is a lack of large sample and multi-center studies.